Cybercrime and society - Yar, Majid (Sage, 2024)
"The fourth edition of Cybercrime and Society provides readers with expert analysis on the most important cybercrime issues affecting modern society. The book has undergone extensive updates and expands on the topics addressed in the 2019 edition, with updated analysis and contemporary case studies on subjects such as: computer hacking, cyberterrorism, hate speech, internet pornography, child sex abuse, and policing the internet. New author Kevin Steinmetz brings further expertise to the book, including an in-depth insight into computer hacking"--